2018
DOI: 10.1097/sap.0000000000001466
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pedicled Perforator Flaps in Chest Reconstruction

Abstract: The possibility of numerous pedicles makes it possible for PPPFs to offset most areas of wall chest defects. Furthermore, this surgical technique is reliable and reproducible, with lower donor site morbidity than that in the case of muscular flaps, which are classically used in this location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In the axillary region, our review of 183 perforator propeller flaps showed a complication rate of 20.2%, with 37 complications. A meta-analysis by Florczak et al [ 81 ] showed an average complication rate of 9.9% for 182 flaps in the thoracic region. In the review by Lazzeri et al [ 82 ] on 288 propeller perforator flaps in the head and neck, trunk, and upper limb regions, the complication rate was 13.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In the axillary region, our review of 183 perforator propeller flaps showed a complication rate of 20.2%, with 37 complications. A meta-analysis by Florczak et al [ 81 ] showed an average complication rate of 9.9% for 182 flaps in the thoracic region. In the review by Lazzeri et al [ 82 ] on 288 propeller perforator flaps in the head and neck, trunk, and upper limb regions, the complication rate was 13.8%.…”
Section: Discussionmentioning
confidence: 99%
“…If still present, the venous congestion can be adequately managed with leech therapy (Herlin et al, 2017). In a previous teams works (Florczak et al, 2018) on PPF for chest wall defect, the SEAP flap had already been associated with a higher complication rate. As previously said, this can rely on intrinsic characteristics of the flap (caliber vessels, length of the pedicle, retrograde vessels flow after CABG), but also on specific characteristics of these patients (arterial disease, smoking status, ASA high score, etc.).…”
Section: Discussionmentioning
confidence: 94%